The probability of a firm making a takeover bid: An empirical analysis of Australian firms - Akhtar, Farida (Sage Publications, 2014)
This study develops a prediction model to investigate the probability of firms making a takeover bid. This model draws upon a number of firm characteristics, which can be categorized under three types of theory: agency costs, hubris behaviour and synergy motives. By examining a sample of 316 Australian publicly listed firms over the period 1999–2010, this study finds that bidding firms are significantly different from non-bidding firms in terms of their cash level, leverage, capital expenditure (long-term productivity growth) and management overconfidence level. Bidding firms are predisposed to enter into takeover activities because their management’s investment decisions are primarily driven by agency, hubris behaviour and synergy motives. The findings show that hubris behaviour is more dominant in influencing managers’ investment decisions in a takeover bid rather than agency or synergy motives.